2019
DOI: 10.3390/nu11010078
|View full text |Cite
|
Sign up to set email alerts
|

Affordability of Food and Beverages in Mexico between 1994 and 2016

Abstract: We estimated the affordability of food and beverages by energy density and nutrient quality in Mexico and tested for differential trends in affordability over time and by income quintile. We used the National Income and Expenditures Survey from 1994 to 2016, and information on the caloric and nutrient content of food and beverages from Mexican food composition tables. We estimated food energy density (kcal/kg) and nutrient quality of food and beverages using the nutrient-rich food index (NRFI). Affordability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…All these exposures from the retail food environment encourage overconsumption, leading to obesity for many [ 38 ]. Acquiring low-nutrient-dense foods that are also calorie-dense has become more accessible and affordable in Mexico [ 24 , 40 ], whilst healthy food is more expensive [ 41 ]. In 2012, the population in Mexico consumed a mean of 163 L of sugar-sweetened beverages (SSB) per person annually, equivalent to 0.5 L/day [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…All these exposures from the retail food environment encourage overconsumption, leading to obesity for many [ 38 ]. Acquiring low-nutrient-dense foods that are also calorie-dense has become more accessible and affordable in Mexico [ 24 , 40 ], whilst healthy food is more expensive [ 41 ]. In 2012, the population in Mexico consumed a mean of 163 L of sugar-sweetened beverages (SSB) per person annually, equivalent to 0.5 L/day [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although this is true for the entire population [ 11 ], there is strong evidence that people with lower socioeconomic status in Argentina consume significantly less fruit, vegetables and dairy and higher amounts of soft drinks and confectionery as compared to the rest of the population [ 12 ]. Despite the unquestionable importance of this information to advocate for effective public health policies targeting environmental determinants of excess weight, evidence on the differential price and affordability of healthier diets is very limited in Latin America with a few notable exceptions [ 13 – 15 ]. This study aimed to bridge this information gap in Argentina by estimating the cost differential and affordability of the current diet vs. healthy diets as of 2018, using the data collection and analysis approach proposed by the International Network for Food and Obesity/non-communicable diseases Research, Monitoring and Action Support (INFORMAS) [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…This transition towards more westernized diets (Popkin 1997) is driven by multiple variables such as food availability and supply, time needed to purchase and cook food, or affordability (Popkin and Gordon-Larsen 2004). In Mexico, Colchero et al (2019) found that energy-dense, industrialized foods with lower nutrient quality were economically more accessible than healthier foods such as fresh produce, especially for lower-income population. Researchers in Mexico have been monitoring this transition because of concerns of the impact of the dietary change on public health.…”
Section: Introductionmentioning
confidence: 99%